2007
DOI: 10.1017/s1744133106006256
|View full text |Cite
|
Sign up to set email alerts
|

Regionalization versus competition in complex cancer surgery

Abstract: The empirical association between high hospital procedure volume and lower mortality rates has led to recommendations for the regionalization of complex surgical procedures. While regionalization may improve outcomes, it also reduces market competition, which has been found to lower prices and improve health care quality. This study estimates the potential net benefits of regionalizing the Whipple surgery for pancreatic cancer patients. We confirm that increased hospital volume and surgeon volume are associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
1
21
0
2
Order By: Relevance
“…[12][13][14][15][16] The declining enthusiasm of surgeons to participate in emergency call has even led to a suggestion to regionalize previously widespread areas of care, such as emergency general surgery. 17 How to balance the advantages of concentrating expertise and experience in specialized medical areas against the need for patients to be expeditiously evaluated and treated is a difficult task, particularly for rural communities in which transport to tertiary referral centers may involve long distances.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] The declining enthusiasm of surgeons to participate in emergency call has even led to a suggestion to regionalize previously widespread areas of care, such as emergency general surgery. 17 How to balance the advantages of concentrating expertise and experience in specialized medical areas against the need for patients to be expeditiously evaluated and treated is a difficult task, particularly for rural communities in which transport to tertiary referral centers may involve long distances.…”
Section: Discussionmentioning
confidence: 99%
“…However, past studies that have accounted for the endogenous relation between hospital volume and mortality or between hospital competition (based on hospital volume) and mortality conclude that the direction of causation is primarily from volume to outcome. 30,31 The analysis does not adjust for differences in patient length of stay, because lower costs may be attributable to shorter hospital stays that are attained after greater surgeon learning. Previous studies suggest that higher surgeon volume is associated with lower mortality measured 30 days postsurgery for several complex cancer operations.…”
Section: Ho and Aloiamentioning
confidence: 99%
“…One limitation of centralized care is that it decreases competition between care providers, and it has been clearly shown that competition between providers in a fixed-price market improves the quality of care, since providers compete in regard to aspects other than price, such as the quality or hospital's amenities (Gaynor & Town, 2012). A study that took into account the changes in the market structure that would occur with centralized care found that regionalization of care for complex cancer surgeries would increase consumer surplus, while controlling for the negative impact of a reduction in competition between providers that it would incur (Ho, Town, & Heslin, 2007a). The second major limitation of centralized care is that it could increase inequalities in access to quality care by increasing in the distance between patients and the site where they receive treatment.…”
Section: Intermediate Factors That Couldmentioning
confidence: 99%
“…Furthermore, failing to properly control for differences in case-mix according to hospital volume activities also makes hospital volume endogenous if they are correlated to patient outcomes. To overcome these econometric issues, several studies have instrumented hospital volume activities by the number of potential patients and other hospitals in a defined area (Gaynor et al, 2005;Gowrisankaran, Ho, & Town, 2006;Hentschker & Mennicken, 2017;Ho, Town, & Heslin, 2007b;Kahn, Ten Have, & Iwashyna, 2009).…”
Section: Introductionmentioning
confidence: 99%